Against the current: Addressing climate-induced health disparities in India's transgender community - Gnana Sanga Mithra S (Science Talks)
This study inspects the unique climate change insights and vulnerabilities experienced by transgender individuals, with an emphasis on how gender identity intermediates environmental awareness and adaptive capacity. A cross-sectional quantitative survey was conducted between January and March 2025 in Chennai, Tamil Nadu, involving 167 self-identified transgender individuals recruited through convenience and snowball sampling methods, accomplishing a response rate of 91 %. Data were collected using a structured questionnaire and analysed using descriptive statistics, t-tests, and Pearson's correlation via SPSS v26. The results showed a health decline score among participants (M = 5.93, SD = 1.27) that was higher than general population norms (t (166) = 5.39, p < 0.001), signifying a discriminating health burden attributable to climate-related stressors. Besides, 79.04 % of respondents articulated a lack of sureness in healthcare provider's' competency concerning transgender-specific health concerns, and 60.47 % reported recurrent or persistent experiences of social isolation. Pearson's correlation analysis identified a statistically significant positive relationship between transgender identity-related stressors and increased apprehension toward climate threats (r = 0.61, p < 0.01).In addition to quantitative findings, qualitative insights from open-ended responses highlighted three emergent themes: (1) Intersecting Marginalities in Climate Vulnerability, reflecting the layered disadvantages faced during environmental disruptions; (2) Systemic Healthcare Exclusion, emphasizing institutional unpreparedness to meet transgender health needs during crises; and (3) Identity-Driven Climate Awareness, representing a delicate sensitivity to climate risks shaped by social and political marginalization. These findings underscore the importance of recognizing transgender individuals as a distinct demographic within climate vulnerability assessments. The study advocates for the combination of marginalized voices in climate adaptation approaches and public health guidelines to guarantee inclusive, equitable, and responsive frameworks in the aspect of mounting environmental challenges.